High-performance double-slurry quick-setting grouting material and preparation method thereof
Modified sulfaluminate cement, hydroxyethylcellulose acrylamide modified bentonite and N-vinylpyrrolidone/methacrylic acid/2-hydroxy-3-methacryloyloxypropylene The base terpolymer, combined with ultraviolet light and crosslinking agent, solves the problems of cracks and low strength after rapid settling of sulfa aluminate cement, and achieves a high-strength and rapid settling grouting material.
Patent Information
- Application Number
- CN202411814604.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-12-11
AI Technical Summary
Sulfur aluminate cement is prone to cracks and low strength after rapid settling.
Methacrylic anhydride gelatin modified sulfa aluminate cement, hydroxyethyl cellulose acrylamide modified bentonite and N-vinylpyrrolidone/methacrylic acid/2-hydroxy-3-methacryloyloxypropyl As the main component, terpolymer combines ultraviolet light, double initiator and crosslinking agent to form a high-strength grouting material to improve its bonding strength and mechanical strength.
The rapid coagulation and high mechanical strength of the grouting material are achieved, which avoids the crack problems that occur after the rapid coagulation of sulfa aluminate cement, and significantly improves the strength of the cement.
Smart Images

Figure CN119263761A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of building materials and relates to a high-performance double-liquid slurry quick-setting grouting material and a preparation method thereof. Background Art
[0002] Grouting material refers to a substance that can be injected into cracks, pores in the ground / layer or gaps and holes in the structure, and plays a role in filling, consolidating and bonding. It is a key material for achieving engineering goals such as strengthening the stratum or structure, preventing seepage and plugging leakage.
[0003] At present, in order to achieve rapid setting performance, sulphoaluminate cement is often used as the main cementitious material for grouting materials. Although sulphoaluminate cement has a fast setting speed, the rapid setting phenomenon not only leads to reduced strength and durability of cement, but also causes unbalanced stress inside cement, which can easily cause cracks inside cement. Summary of the invention
[0004] The purpose of the present invention is to provide a high-performance dual-liquid slurry rapid-setting grouting material and a preparation method thereof, so as to solve the problem that cracks are easily formed inside the sulphoaluminate cement after rapid setting and the strength is low.
[0005] The technical solution adopted by the present invention is as follows: A high-performance dual-liquid slurry rapid-setting grouting material, comprising component A and component B, wherein component A is a base slurry, and component B is a performance regulator for component A; The component A comprises the following components in parts by weight: 30-35 parts of methacrylic anhydride gelatin modified sulphoaluminate cement, 5-8 parts of calcium powder, 0.25-0.45 parts of lanthanum cerium oxide, 0.5-0.8 parts of amino acid type surfactant activator, 1-1.5 parts of polycarboxylate water reducer, and water, wherein the water-cement ratio of water to modified sulphoaluminate cement is 0.35-0.45; The component B comprises the following components: hydroxyethyl cellulose acrylamide modified bentonite, N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride terpolymer, a double initiator, a crosslinking agent, and deionized water; The mass ratio of hydroxyethyl cellulose acrylamide modified bentonite, methacrylic anhydride gelatin modified sulphoaluminate cement, and N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyltrimethylammonium chloride terpolymer is 2:8:1; The dual initiator comprises: a redox initiator and a photoinitiator, wherein the mass ratio of the redox initiator to the photoinitiator is 1:1.2-1.5; the amount of the dual initiator added is 0.4-0.5% of the sum of the mass of the terpolymer of hydroxyethyl cellulose acrylamide modified bentonite, methacrylic anhydride gelatin modified sulphoaluminate cement, and N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethylammonium chloride; The cross-linking agent comprises TG enzyme and tannic acid, the mass ratio of TG enzyme and tannic acid is 3:2, and the amount of the cross-linking agent added is 1-1.2% of the methacrylic anhydride gelatin modified sulphoaluminate cement.
[0006] In the present invention, methacrylic anhydride gelatin modified sulphoaluminate cement is used as the main component of the base slurry. Sulphoaluminate cement has the characteristics of early strength and high strength. The modification of methacrylic anhydride gelatin further enhances its bonding force and crack resistance, which helps to reduce the formation of cracks. In addition, under the action of ultraviolet irradiation and photoinitiator, methacrylic anhydride gelatin can be photocured with a fast curing speed. As a filler, calcium powder can improve the density and strength of the grouting material. Amino acid type surfactant stimulator can reduce the surface tension of cement particles, promote the dispersion and hydration of cement particles, thereby improving the strength and fluidity of the grouting material. Adding bentonite to cement can play a role in preventing leakage, but the compatibility between bentonite and cement is poor, which makes the dispersibility of bentonite in cement poor. Therefore, the present invention adopts hydroxyethyl cellulose acrylamide modified bentonite. After hydroxyethyl cellulose acrylamide modification, The bentonite has good dispersibility in cement slurry; in order to strengthen the connectivity between the bentonite modified by hydroxyethyl cellulose acrylamide and the sulphoaluminate cement modified by methacrylic anhydride gelatin, the present invention adds an N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride terpolymer, the N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride terpolymer has good water solubility and a stable structure, the N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride terpolymer is polymerized and cross-linked with methacrylic anhydride gelatin and hydroxyethyl cellulose acrylamide under the action of an initiator and a cross-linking agent, and a stable three-dimensional network structure can be formed, which can not only strengthen the bonding strength of the entire grouting material system but also improve the mechanical strength of the grouting material.
[0007] The present invention uses methacrylic anhydride gelatin modified sulphoaluminate cement, hydroxyethyl cellulose acrylamide modified bentonite, N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride terpolymer as main components, and under the action of ultraviolet light, a double initiator, and a cross-linking agent, a high-strength grouting material can be formed, and the setting speed is fast. The cross-linking in the present invention is TG enzyme and tannic acid. Adding TG enzyme and tannic acid to gelatin can significantly improve the gel strength, and then can significantly improve the strength of gelatin-modified cement; in addition, tannic acid can also form hydrogen bonds with hydroxyethyl cellulose molecular chains to form a dense hydrogen bond network.
[0008] In the terpolymer of N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride, N-vinyl pyrrolidone as a non-ionic hydrophilic monomer can improve the hydrophilicity, transparency and flexibility of the copolymer. At the same time, N-vinyl pyrrolidone also has good copolymerization and reactivity, and can form a stable copolymer with methacrylic acid and 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride (HMOPTA); methacrylic acid has good compatibility with methacrylic anhydride gelatin, and can undergo cross-linking polymerization under ultraviolet light and photoinitiator, thereby strengthening the connection strength between the terpolymer and methacrylic anhydride gelatin; 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride contains multiple functional groups, has high reactivity, can participate in polymerization reactions, improve the stability of the copolymer, and adapt to various environments.
[0009] Furthermore, the methacrylic anhydride gelatin modified sulphoaluminate cement is prepared by the following method: S1. Using methacrylic anhydride and gelatin as raw materials to prepare methacrylic anhydride gelatin, adding the methacrylic anhydride gelatin into a phosphate buffer solution, stirring at 40° C. for 30-40 minutes, adding a silane coupling agent, and continuing to stir for 20-30 minutes to obtain a methacrylic anhydride gelatin solution; S2, grinding the sulphoaluminate cement clinker to obtain sulphoaluminate cement powder; S3. Place sulphoaluminate cement powder in a mixing tank, maintain the temperature in the mixing tank at 40-50°C under stirring at 150 rpm, use a spray gun to spray the methacrylic anhydride gelatin solution into the mixing tank at a spray pressure of 0.4 MPa, so that the methacrylic anhydride gelatin adheres to the surface of the sulphoaluminate cement particles, and dry at 55-60°C after spraying to obtain methacrylic anhydride gelatin-modified sulphoaluminate cement particles.
[0010] Furthermore, the hydroxyethyl cellulose acrylamide modified bentonite is prepared by the following method: Preparation of hydroxyethyl cellulose-acrylamide graft polymer: hydroxyethyl cellulose and acrylamide are dispersed in deionized water and stirred on a magnetic stirrer, and then the pH is adjusted to 7 with a sodium hydroxide solution, and then the stirred solution is poured into a three-necked long-necked flask, and then an initiator is added, and the solution is placed in a MAS-Ⅱ microwave synthesis reaction station for synthesis reaction. The parameters of the synthesis reaction are preset to 40°C, 60 h, 200 W, and nitrogen is introduced. Under the action of magnetic stirring, a transparent colloidal liquid is obtained through synthesis reaction. After standing to room temperature, the reactant is precipitated with ethanol, and the precipitate is filtered after multiple washing to obtain a precipitate. The precipitate is dried to constant weight under a vacuum state at 70°C, and then purified with acetone in a Soxhlet extractor for 10 h. Finally, the precipitate is dried again to constant weight, and ground into powder in a YXQM planetary ball mill to obtain a hydroxyethyl cellulose-acrylamide graft polymer; Hydroxyethyl cellulose-acrylamide graft polymer modified bentonite: sodium bentonite was dispersed in deionized water, and 3 wt% of hydroxyethyl cellulose-acrylamide graft polymer was added after the dispersion was fully stirred. 3 The mixture was vigorously stirred at a speed of rpm for 2 h, and finally dried in a drying oven at 105°C±3°C to constant weight, and then ground to obtain hydroxyethyl cellulose acrylamide modified bentonite.
[0011] Furthermore, the mass ratio of hydroxyethyl cellulose to acrylamide is 1:10, and ammonium persulfate and sodium bisulfite are used as initiators.
[0012] Furthermore, the component A also includes 0.06-0.08 parts of sodium citrate, 0.08-0.13 parts of sorbitol, and 1-2 parts of silica fume.
[0013] Furthermore, the preparation method of the N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyltrimethylammonium chloride terpolymer is as follows: N-vinyl pyrrolidone is dissolved in water, methacrylic acid is added and stirred evenly, and then sodium hydroxide is used to adjust the pH to 7, and then 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride is added and stirred evenly to obtain a reaction solution; the reaction solution is added to a reaction container equipped with a stirrer, a thermometer and a nitrogen inlet, the temperature is increased and stirred, nitrogen is introduced, and the nitrogen introduction is stopped after the temperature is increased to 60° C., and potassium persulfate is added as an initiator, and the amount of potassium persulfate added is the total amount of N-vinyl pyrrolidone, methacrylic acid, and 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride. The reaction mixture was stirred for 2 hours at 60°C for 0.5% by weight, and then 6-tert-butyl-2,4-dimethylphenol was added as a polymerization inhibitor. The amount of 6-tert-butyl-2,4-dimethylphenol polymerization inhibitor added was 0.02% of the total mass of N-vinyl pyrrolidone, methacrylic acid, and 2-hydroxy-3-methacryloxypropyltrimethylammonium chloride. The reaction solution was then cooled to room temperature, precipitated, washed, dried, and crushed to obtain a terpolymer of N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyltrimethylammonium chloride.
[0014] Furthermore, the amino acid type surfactant stimulant includes sodium lauroyl glutamate and sodium cocoyl alanine, and the mass ratio of sodium lauroyl glutamate to sodium cocoyl alanine is 3:2.
[0015] Furthermore, the redox initiator is an ammonium persulfate-sodium bisulfite redox agent; the photoinitiator includes 4,4'-dihydroxybenzophenone and nano-titanium dioxide, and the mass ratio of 4,4'-dihydroxybenzophenone to nano-titanium dioxide is 1:1.
[0016] A method for preparing a high-performance dual-liquid slurry rapid-setting grouting material comprises the following steps: A. Preparing a first slurry: Component A is used as a raw material to prepare a first slurry. Sulphoaluminate cement modified with methacrylic anhydride gelatin and calcium powder are uniformly mixed to form a mixed powder. A corresponding amount of water is weighed according to the water-cement ratio. The water is first added to a mixing tank. Then, a stirrer matched with the mixing tank is turned on. The speed of the stirrer is 250 r / min. The internal temperature of the mixing tank is 35-40° C. The mixed powder is slowly added to the mixing tank at a speed of 250 r / min. After the mixed powder is added, the other components of component A are added to the mixing tank in sequence while the stirrer is continuously stirred. The stirring is continued for 10 minutes and then allowed to stand for 10 minutes to obtain a first slurry. B. Preparing a second slurry: dispersing the hydroxyethyl cellulose acrylamide modified bentonite in component B in water to obtain a bentonite dispersion; adding the N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride terpolymer in component B to water, heating to 50° C. under stirring, stirring at a constant temperature for 5-6 minutes, and then standing to cool to room temperature to obtain a N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride terpolymer solution; slowly pouring the N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride terpolymer solution into the bentonite dispersion under stirring, stirring evenly to obtain a second slurry; C. At a rotation speed of 250 r / min, the first slurry and the second slurry are uniformly mixed, and then the dual initiator and the cross-linking agent in component B are added in sequence, and the target product is obtained after uniform stirring. The target product is a high-performance two-liquid slurry rapid-setting grouting material. The high-performance two-liquid slurry rapid-setting grouting material is used within 5 minutes after successful preparation. The high-performance two-liquid slurry rapid-setting grouting material is irradiated with ultraviolet light with a wavelength of 280-340 nm for 3-5 minutes in the initial stage of curing after the grouting is completed, so that the initial setting time of the high-performance two-liquid slurry rapid-setting grouting material is within 8 minutes, and the final setting time is 0.4-0.6h.
[0017] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. The present invention uses methacrylic anhydride gelatin modified sulphoaluminate cement, hydroxyethyl cellulose acrylamide modified bentonite, N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethylammonium chloride terpolymer as main components, and under the action of ultraviolet light, a double initiator, and a cross-linking agent, a high-strength grouting material can be formed, and the setting speed is fast; 2. The cross-linking in the present invention is TG enzyme and tannic acid. Adding TG enzyme and tannic acid to gelatin can significantly improve the gel strength, and thus significantly improve the strength of gelatin-modified cement. Tannic acid can also form hydrogen bonds with hydroxyethyl cellulose molecular chains to form a dense hydrogen bond network. 3. The N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride terpolymer in the present invention has good water solubility and stable structure. The N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride terpolymer is polymerized and cross-linked with methacrylic anhydride gelatin and hydroxyethyl cellulose acrylamide under the action of an initiator and a cross-linking agent to form a three-dimensional network structure with a stable structure, which can not only enhance the bonding strength of the entire grouting material system but also improve the mechanical strength of the grouting material. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative work, among which: Figure 1 This is a cross-sectional SEM image of the grouting material prepared in Example 4 after curing for 28 days. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings herein can be arranged and designed in various different configurations.
[0020] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present invention.
[0021] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0022] The features and performance of the present invention are further described in detail below in conjunction with the embodiments. Example 1
[0023] A high-performance dual-liquid slurry rapid-setting grouting material provided in a preferred embodiment of the present invention comprises component A and component B, wherein component A is a base slurry and component B is a performance regulator for component A; The component A comprises the following components in parts by weight: 30 parts of methacrylic anhydride gelatin modified sulphoaluminate cement, 5 parts of calcium powder, 0.25 parts of lanthanum cerium oxide, 0.5 parts of amino acid type surfactant activator, 1 part of polycarboxylic acid water reducer, water, 0.06 parts of sodium citrate, 0.08 parts of sorbitol, and 1 part of silica fume, wherein the water-cement ratio of water to modified sulphoaluminate cement is 0.35, and the polycarboxylic acid water reducer is a polyamide-polyethylene glycol branched amphoteric water reducer; The component B comprises the following components: hydroxyethyl cellulose acrylamide modified bentonite, N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride terpolymer, a dual initiator, a crosslinking agent, and deionized water; wherein the redox initiator is an ammonium persulfate-sodium bisulfite redox agent; the photoinitiator comprises 4,4'-dihydroxybenzophenone and nano titanium dioxide, and the mass ratio of 4,4'-dihydroxybenzophenone to nano titanium dioxide is 1:1; The mass ratio of hydroxyethyl cellulose acrylamide modified bentonite, methacrylic anhydride gelatin modified sulphoaluminate cement, and N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyltrimethylammonium chloride terpolymer is 2:8:1; The dual initiator comprises: a redox initiator and a photoinitiator, wherein the mass ratio of the redox initiator to the photoinitiator is 1:1.2; the amount of the dual initiator added is 0.4 of the sum of the mass of the terpolymer of hydroxyethyl cellulose acrylamide modified bentonite, methacrylic anhydride gelatin modified sulphoaluminate cement, and N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethylammonium chloride; The cross-linking agent comprises TG enzyme and tannic acid, the mass ratio of TG enzyme and tannic acid is 3:2, and the amount of the cross-linking agent added is 1% of the methacrylic anhydride gelatin modified sulphoaluminate cement.
[0024] The methacrylic anhydride gelatin modified sulphoaluminate cement is prepared by the following method: S1. Using methacrylic anhydride and gelatin as raw materials to prepare methacrylic anhydride gelatin, adding the methacrylic anhydride gelatin into a phosphate buffer solution, stirring at 40° C. for 30-40 minutes, adding a silane coupling agent, and continuing to stir for 20-30 minutes to obtain a methacrylic anhydride gelatin solution, wherein the silane coupling agent is a KH550 aminosilane coupling agent; S2, grinding the sulphoaluminate cement clinker to obtain sulphoaluminate cement powder; S3. Place sulphoaluminate cement powder in a mixing tank, maintain the temperature in the mixing tank at 40-50°C under stirring at 150 rpm, use a spray gun to spray the methacrylic anhydride gelatin solution into the mixing tank at a spray pressure of 0.4 MPa, so that the methacrylic anhydride gelatin adheres to the surface of the sulphoaluminate cement particles, and dry at 55-60°C after spraying to obtain methacrylic anhydride gelatin-modified sulphoaluminate cement particles.
[0025] The hydroxyethyl cellulose acrylamide modified bentonite is prepared by the following method: Preparation of hydroxyethyl cellulose-acrylamide graft polymer: hydroxyethyl cellulose and acrylamide are dispersed in deionized water and stirred on a magnetic stirrer, and then the pH is adjusted to 7 with a sodium hydroxide solution, and then the stirred solution is poured into a three-necked long-necked flask, and then an initiator is added, and the solution is placed in a MAS-Ⅱ microwave synthesis reaction station for synthesis reaction. The parameters of the synthesis reaction are preset to 40°C, 60 h, 200 W, and nitrogen is introduced. Under the action of magnetic stirring, a transparent colloidal liquid is obtained through synthesis reaction. After standing to room temperature, the reactant is precipitated with ethanol, and the precipitate is filtered after multiple washing to obtain a precipitate. The precipitate is dried to constant weight under a vacuum state at 70°C, and then purified with acetone in a Soxhlet extractor for 10 h. Finally, the precipitate is dried again to constant weight, and ground into powder in a YXQM planetary ball mill to obtain a hydroxyethyl cellulose-acrylamide graft polymer; Hydroxyethyl cellulose-acrylamide graft polymer modified bentonite: sodium bentonite was dispersed in deionized water, and 3 wt% of hydroxyethyl cellulose-acrylamide graft polymer was added after the dispersion was fully stirred. 3 The mixture was vigorously stirred at a speed of rpm for 2 hours, and finally dried in a drying oven at 105°C±3°C to constant weight, and then ground to obtain hydroxyethyl cellulose acrylamide modified bentonite, wherein the mass ratio of hydroxyethyl cellulose to acrylamide was 1:10, and ammonium persulfate and sodium bisulfite were used as initiators.
[0026] The preparation method of the N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyltrimethylammonium chloride terpolymer is as follows: N-vinyl pyrrolidone is dissolved in water, methacrylic acid is added and stirred evenly, and then sodium hydroxide is used to adjust the pH to 7, and then 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride is added and stirred evenly to obtain a reaction solution; the reaction solution is added to a reaction container equipped with a stirrer, a thermometer and a nitrogen inlet, the temperature is increased and stirred, nitrogen is introduced, and the nitrogen introduction is stopped after the temperature is increased to 60° C., and potassium persulfate is added as an initiator, and the amount of potassium persulfate added is the total amount of N-vinyl pyrrolidone, methacrylic acid, and 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride. The reaction mixture was stirred for 2 hours at 60°C for 0.5% by weight, and then 6-tert-butyl-2,4-dimethylphenol was added as a polymerization inhibitor. The amount of 6-tert-butyl-2,4-dimethylphenol polymerization inhibitor added was 0.02% of the total mass of N-vinyl pyrrolidone, methacrylic acid, and 2-hydroxy-3-methacryloxypropyltrimethylammonium chloride. The reaction solution was then cooled to room temperature, precipitated, washed, dried, and crushed to obtain a terpolymer of N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyltrimethylammonium chloride.
[0027] The amino acid type surfactant stimulant includes sodium lauroyl glutamate and sodium cocoyl alanine, and the mass ratio of sodium lauroyl glutamate to sodium cocoyl alanine is 3:2.
[0028] The above-mentioned method for preparing a high-performance dual-liquid slurry rapid-setting grouting material comprises the following steps: A. Preparing a first slurry: Component A is used as a raw material to prepare a first slurry. Sulphoaluminate cement modified with methacrylic anhydride gelatin and calcium powder are uniformly mixed to form a mixed powder. A corresponding amount of water is weighed according to the water-cement ratio. The water is first added to a mixing tank. Then, a stirrer matched with the mixing tank is turned on. The speed of the stirrer is 250 r / min. The internal temperature of the mixing tank is 35-40° C. The mixed powder is slowly added to the mixing tank at a speed of 250 r / min. After the mixed powder is added, the other components of component A are added to the mixing tank in sequence while the stirrer is continuously stirred. The stirring is continued for 10 minutes and then allowed to stand for 10 minutes to obtain a first slurry. B. Preparing a second slurry: dispersing the hydroxyethyl cellulose acrylamide modified bentonite in component B in water to obtain a bentonite dispersion; adding the N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride terpolymer in component B to water, heating to 50° C. under stirring, stirring at a constant temperature for 5-6 minutes, and then standing to cool to room temperature to obtain a N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride terpolymer solution; slowly pouring the N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride terpolymer solution into the bentonite dispersion under stirring, stirring evenly to obtain a second slurry; C. At a rotation speed of 250 r / min, the first slurry and the second slurry are uniformly mixed, and then the dual initiator and the cross-linking agent in component B are added in sequence, and the target product is obtained after stirring evenly. The target product is a high-performance dual-liquid slurry rapid-setting grouting material, and the high-performance dual-liquid slurry rapid-setting grouting material is used within 5 minutes after successful preparation.
[0029] The high-performance double-liquid slurry fast-setting grouting material is irradiated with ultraviolet light with a wavelength of 280-340nm for 3-5 minutes in the initial stage of curing after grouting is completed, so that the initial setting time of the high-performance double-liquid slurry fast-setting grouting material is within 8 minutes and the final setting time is 0.4-0.6h. Example 2
[0030] This embodiment is based on the embodiment 1, and is different from the embodiment 1 in that: this embodiment provides a high-performance dual-liquid slurry rapid setting grouting material, including component A and component B, wherein component A is a base slurry, and component B is a performance regulator for component A; The component A comprises the following components in parts by weight: 32.5 parts of methacrylic anhydride gelatin modified sulphoaluminate cement, 6.5 parts of calcium powder, 0.35 parts of lanthanum cerium oxide, 0.7 parts of amino acid type surfactant activator, 1.3 parts of polycarboxylic acid water reducer, water, 0.07 parts of sodium citrate, 0.1 parts of sorbitol, and 1.5 parts of silica fume, wherein the water-cement ratio of water to modified sulphoaluminate cement is 0.40. Too large or too small a water-cement ratio will affect the strength of the cement; if the water-cement ratio is too large, the moisture content is high and the strength is low; if the water-cement ratio is too small, the cement particles cannot be fully hydrated and the strength is low; therefore, the present invention preferably selects the optimal water-cement ratio.
[0031] The component B comprises the following components: hydroxyethyl cellulose acrylamide modified bentonite, N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride terpolymer, a double initiator, a crosslinking agent, and deionized water; The mass ratio of hydroxyethyl cellulose acrylamide modified bentonite, methacrylic anhydride gelatin modified sulphoaluminate cement, and N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyltrimethylammonium chloride terpolymer is 2:8:1; The dual initiator comprises: a redox initiator and a photoinitiator, wherein the mass ratio of the redox initiator to the photoinitiator is 1:1.4; the amount of the dual initiator added is 0.4% of the sum of the mass of the terpolymer of hydroxyethyl cellulose acrylamide modified bentonite, methacrylic anhydride gelatin modified sulphoaluminate cement, and N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethylammonium chloride; The cross-linking agent comprises TG enzyme and tannic acid, the mass ratio of TG enzyme and tannic acid is 3:2, and the amount of the cross-linking agent added is 1.1% of the methacrylic anhydride gelatin modified sulphoaluminate cement. Example 3
[0032] This embodiment is based on the embodiment 1, and is different from the embodiment 1 in that: this embodiment provides a high-performance dual-liquid slurry rapid setting grouting material, including component A and component B, wherein component A is a base slurry, and component B is a performance regulator for component A; The component A comprises the following components in parts by weight: 35 parts of methacrylic anhydride gelatin modified sulphoaluminate cement, 8 parts of calcium powder, 0.45 parts of lanthanum cerium oxide, 0.8 parts of amino acid type surfactant activator, 1.5 parts of polycarboxylate water reducer, water, 0.08 parts of sodium citrate, 0.13 parts of sorbitol, and 2 parts of silica fume, wherein the water-cement ratio of water to modified sulphoaluminate cement is 0.45; The component B comprises the following components: hydroxyethyl cellulose acrylamide modified bentonite, N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride terpolymer, a double initiator, a crosslinking agent, and deionized water; The mass ratio of hydroxyethyl cellulose acrylamide modified bentonite, methacrylic anhydride gelatin modified sulphoaluminate cement, and N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyltrimethylammonium chloride terpolymer is 2:8:1; The dual initiator comprises: a redox initiator and a photoinitiator, wherein the mass ratio of the redox initiator to the photoinitiator is 1:1.5; the amount of the dual initiator added is 0.5% of the sum of the mass of the terpolymer of hydroxyethyl cellulose acrylamide modified bentonite, methacrylic anhydride gelatin modified sulphoaluminate cement, and N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethylammonium chloride; The cross-linking agent comprises TG enzyme and tannic acid, the mass ratio of TG enzyme and tannic acid is 3:2, and the amount of the cross-linking agent added is 1.2% of the methacrylic anhydride gelatin modified sulphoaluminate cement. Example 4
[0033] Based on Example 2, the difference from Example 2 is that the water-cement ratio of water to modified sulphoaluminate cement in component A is 0.45. The SEM micrograph of the grouting material obtained in this example after 28 days (28 days) is as follows: Figure 1 As shown, there are no cracks or splits. Example 5
[0034] Based on Example 2, the difference from Example 2 is that the water-cement ratio of water to modified sulphoaluminate cement in component A is 0.35. Example 6
[0035] Based on Example 2, the difference from Example 2 is that the dual initiator includes: a redox initiator and a photoinitiator, and the mass ratio of the redox initiator to the photoinitiator is 1:1.2. Example 7
[0036] Based on Example 2, the difference from Example 2 is that the dual initiator includes: a redox initiator and a photoinitiator, and the mass ratio of the redox initiator to the photoinitiator is 1:1.5. Example 8
[0037] Based on Example 2, the difference from Example 2 is that the added amount of the dual initiator is 0.5% of the sum of the mass of the terpolymer of hydroxyethyl cellulose acrylamide modified bentonite, methacrylic anhydride modified gelatin sulphoaluminate cement, and N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyltrimethylammonium chloride. Comparative Example 1
[0038] Based on Example 2, the difference from Example 2 is that this comparative example does not include component B, and only component A is used to prepare the quick-setting grouting material. Comparative Example 2
[0039] Based on Example 2, the difference from Example 2 is that the water-cement ratio of water to modified sulphoaluminate cement in component A of this comparative example is 0.5. Comparative Example 3
[0040] Based on Example 2, the difference from Example 2 is that the water-cement ratio of water to modified sulphoaluminate cement in component A of this comparative example is 0.3. Comparative Example 4
[0041] Based on Example 4, the difference from Example 4 is that the amount of the diinitiator added in this comparative example is 0.3% of the sum of the mass of the terpolymer of hydroxyethyl cellulose acrylamide modified bentonite, methacrylic anhydride modified gelatin sulphoaluminate cement, and N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyltrimethylammonium chloride. Comparative Example 5
[0042] Based on Example 1, the difference from Example 1 is that the sulphoaluminate cement in component A is unmodified sulphoaluminate cement, and the sulphoaluminate cement used is 42.5 strength grade sulphoaluminate cement. Comparative Example 6
[0043] Based on Example 4, the difference from Example 4 is that the cross-linking agent in component B includes TG enzyme and tannic acid, and the mass ratio of TG enzyme to tannic acid is 2:1. Comparative Example 7
[0044] Based on Example 4, the difference from Example 4 is that: the cross-linking agent in component B includes TG enzyme and tannic acid, and the mass ratio of TG enzyme to tannic acid is 1:1. Comparative Example 8
[0045] Based on Example 4, the difference from Example 4 is that the bentonite in component B is unmodified sodium bentonite. Comparative Example 9
[0046] Based on Example 4, the difference from Example 4 is that the component B does not include the N-vinylpyrrolidone methacrylic acid / 2-hydroxy-3-methacryloxypropyltrimethylammonium chloride terpolymer. Comparative Example 10
[0047] Based on Example 4, the difference from Example 4 is that the component B does not include hydroxyethyl cellulose acrylamide modified bentonite. Comparative Example 11
[0048] Based on Example 4, the difference from Example 4 is that the initiator in component B does not use a dual initiator, but only a single redox initiator. Comparative Example 12
[0049] Based on Example 4, the difference from Example 4 is that the initiator in component B does not use a dual initiator, but only a single photoinitiator. Comparative Example 13
[0050] Based on Example 4, the difference from Example 4 is that no crosslinking agent is added to the component B. Comparative Example 14
[0051] Based on Example 4, the difference from Example 4 is that the cross-linking agent in component B only uses TG enzyme. Comparative Example 15
[0052] Based on Example 4, the difference from Example 4 is that the cross-linking agent in component B is only tannic acid. Comparative Example 16
[0053] Based on Example 4, the difference from Example 4 is that the amino acid type surfactant stimulant includes sodium lauroyl glutamate and sodium cocoyl alanine, and the mass ratio of sodium lauroyl glutamate to sodium cocoyl alanine is 2:1. Comparative Example 17
[0054] Based on Example 4, the difference from Example 4 is that the amino acid type surfactant stimulant includes sodium lauroyl glutamate and sodium cocoyl alanine, and the mass ratio of sodium lauroyl glutamate to sodium cocoyl alanine is 1:1. Comparative Example 18
[0055] Based on Example 4, the difference from Example 4 is that the amino acid type surfactant stimulator does not include sodium lauroyl glutamate. Comparative Example 19
[0056] Based on Example 4, the difference from Example 4 is that the amino acid type surfactant stimulant does not include sodium cocoyl alanine. Comparative Example 20
[0057] Based on Example 4, the difference from Example 4 is that the mass ratio of hydroxyethyl cellulose acrylamide modified bentonite, methacrylic anhydride gelatin modified sulphoaluminate cement, and N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyltrimethylammonium chloride terpolymer is 1:8:1. Comparative Example 21
[0058] Based on Example 4, the difference from Example 4 is that the mass ratio of hydroxyethyl cellulose acrylamide modified bentonite, methacrylic anhydride gelatin modified sulphoaluminate cement, and N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyltrimethylammonium chloride terpolymer is 3:8:1. Comparative Example 22
[0059] Based on Example 4, the difference from Example 4 is that the mass ratio of hydroxyethyl cellulose acrylamide modified bentonite, methacrylic anhydride gelatin modified sulphoaluminate cement, and N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyltrimethylammonium chloride terpolymer is 2:8:2. Comparative Example 23
[0060] Based on Example 4, the difference from Example 4 is that the mass ratio of hydroxyethyl cellulose acrylamide modified bentonite, methacrylic anhydride gelatin modified sulphoaluminate cement, and N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyltrimethylammonium chloride terpolymer is 2:8:0.5. Test Example 1
[0061] The initial setting time and final setting time of the grouting materials prepared in Examples 1-8 and Comparative Examples 1-23 were measured. The method for measuring the initial setting time and final setting time of the grouting materials was based on the method for measuring the initial setting time and final setting time of polymer cement mortar. The measuring method is the prior art. The measuring results are shown in Table 1. The initial setting time and final setting time were measured after the grouting materials were irradiated with ultraviolet light with a wavelength of 280-340 nm for 3-5 minutes in the initial stage of curing.
[0062] Table 1 Initial and final setting time of grouting material Initial setting time Final setting time Example 1 <8min 0.5-0.6h Example 2 <8min 0.5-0.6h Example 3 <8min 0.5-0.6h Example 4 <8min 0.4-0.5h Example 5 <8min 0.5-0.6h Example 6 <8min 0.5-0.6h Example 7 <8min 0.5-0.6h Example 8 <8min 0.5-0.6h Comparative Example 1 30-32min 1-1.2h Comparative Example 2 33-35min 1.3-1.5h Comparative Example 3 <8min 0.5-0.6h Comparative Example 4 20-22min 1-1.2h Comparative Example 5 60-65min 4-5h Comparative Example 6 <8min 0.6-0.8h Comparative Example 7 <8min 0.5-0.6h Comparative Example 8 50-52min 1.4-1.5h Comparative Example 9 40-42min 1.2-1.3h Comparative Example 10 30-32min 1-1.2h Comparative Example 11 55-56min 2-2.5h Comparative Example 12 40-41min 1.6-1.7h Comparative Example 13 52-53min 2-2.2h Comparative Example 14 35-38min 1.3-1.4h Comparative Example 15 42-44min 2-2.1h Comparative Example 16 <8min 0.6-0.8h Comparative Example 17 15-18min 1-1.1h Comparative Example 18 40-41min 2.5-2.6h Comparative Example 19 50-52min 3-3.1h Comparative Example 20 25-26min 1.1-1.2h Comparative Example 21 40-42min 1.4-1.5h Comparative Example 22 <8min 0.8-1h Comparative Example 23 <8min 0.5-0.6h It is irradiated with ultraviolet light with a wavelength of 280-340nm for 3-5 minutes, so that the initial setting time of the high-performance double-liquid slurry quick-setting grouting material is within 8 minutes, and the final setting time is 0.4-0.6h. During the ultraviolet irradiation process, the grouting material of the present invention can be promoted to set quickly, and has strong mechanical strength after setting. Test Example 2
[0063] Referring to the standard DL / T5126-2021 "Test Procedure for Polymer Modified Cement Mortar", the strength of the grouting materials prepared in Examples 1-8 and Comparative Examples 1-23 was measured. The detection method is the prior art, reference patent: 202311193743.0. The results are shown in Table 2.
[0064] Table 2 Strength test results of grouting materials 3h compressive strengthMpa 5h compressive strengthMpa 1d compressive strengthMpa 28d compressive strength Mpa 28d flexural strength Mpa 2h bonding strengthMpa Example 1 33-34 38-39 48-49 88.5-88.75 >10 >2 Example 2 34-35 40-41 50-51 89-90 >10 >2 Example 3 33-34 37-38 47-48 88.5-88.75 >10 >2 Example 4 >35 46-47 53-54 >89 >10 >2 Example 5 33-34 40-41 48-49 88.75-89 >10 >2 Example 6 33-34 37-38 48-49 88.7-89 >10 >2 Example 7 34-35 40-41 49-50 89-90 >10 >2 Example 8 34-35 41-42 50-51 89-90 >10 >2 Comparative Example 1 25-26 30-31 34-35.5 53.5-54 6.8-7 >2 Comparative Example 2 24-25 28-30 32-33 47.5-48 4-6 >2 Comparative Example 3 25-26 31-31.5 34-35 52-53 6.8-7 <2 Comparative Example 4 32-33 37-38 45-46 85-86 7-8 >2 Comparative Example 5 20-22 24-25 30-31 43-44 4-6 <2 Comparative Example 6 >35 46-47 50-51 88.5-88.7 >10 >2 Comparative Example 7 >35 45-46.5 51-52 87-88 7-8 <2 Comparative Example 8 25-26 30-32 50-51 89-90 >10 >2 Comparative Example 9 30-31 34-35 45-46 60-61 6-8 <2 Comparative Example 10 26-27 32-33 42.5-43 57-58 9-10 >2 Comparative Example 11 25-25.5 30-31 45-46.5 62-63 >10 <2 Comparative Example 12 34-35 41-42 47-48 64-65 >10 <2 Comparative Example 13 34-35 37-38 46-46.5 70-7.5 >10 <2 Comparative Example 14 29-30 37.5-38 47-48 80-82 >10 >2 Comparative Example 15 30-31 37.5-38 45-46 76-77 >10 >2 Comparative Example 16 >35 40-41 53-54 89-90 >10 >2 Comparative Example 17 33-34 37-38 47-48 88.5-89 >10 >2 Comparative Example 18 32.5-33 38-39 47.5-48 82-83 >10 >2 Comparative Example 19 33-34 40-41 48-49 85-86 >10 >2 Comparative Example 20 32-33 37-38 45-46 84-85 7-8 >2 Comparative Example 21 27-28 30-31 50-51 87-88 >10 >2 Comparative Example 22 >35 44-45 50-50.5 80-81 >10 <2 Comparative Example 23 >35 46-47 53-54 87-88 8-9 <2 Combining the data in Table 1 and Table 2, it can be seen that Example 4 in the present invention is the best ratio. The strength of the grouting material in the present invention is greater than 89MPa, the flexural strength is greater than 10MPa, and the bonding strength after 2h is greater than 2MPa; the SEM micrograph of the grouting material obtained in Example 4 after 28d (28 days) is as follows: Figure 1 As shown, there are no cracks or splits.
[0065] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions and improvements made by any technician familiar with the field within the spirit and principle of the present invention should be included in the scope of protection of the present invention.
Claims
1. A high-performance dual-liquid slurry rapid-setting grouting material, characterized in that: It comprises component A and component B, wherein component A is a base slurry, and component B is a performance regulator for component A; The component A comprises the following components in parts by weight: 30-35 parts of methacrylic anhydride gelatin modified sulphoaluminate cement, 5-8 parts of calcium powder, 0.25-0.45 parts of lanthanum oxide cerium, 0.5-0.8 parts of amino acid type surfactant activator, 1-1.5 parts of polycarboxylate water reducer, and water, wherein the water-cement ratio of water to methacrylic anhydride gelatin modified sulphoaluminate cement is 0.35-0.45; The component B comprises the following components: hydroxyethyl cellulose acrylamide modified bentonite, N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride terpolymer, a double initiator, a crosslinking agent, and deionized water; The mass ratio of hydroxyethyl cellulose acrylamide modified bentonite, methacrylic anhydride gelatin modified sulphoaluminate cement, and N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyltrimethylammonium chloride terpolymer is 2:8:1; The dual initiator comprises: a redox initiator and a photoinitiator, wherein the mass ratio of the redox initiator to the photoinitiator is 1:1.2-1.5; the amount of the dual initiator added is 0.4-0.5% of the sum of the mass of the terpolymer of hydroxyethyl cellulose acrylamide modified bentonite, methacrylic anhydride gelatin modified sulphoaluminate cement, and N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethylammonium chloride; The cross-linking agent comprises TG enzyme and tannic acid, the mass ratio of TG enzyme and tannic acid is 3:2, and the amount of the cross-linking agent added is 1-1.2% of the methacrylic anhydride gelatin modified sulphoaluminate cement.
2. A high-performance dual-liquid slurry rapid-setting grouting material according to claim 1, characterized in that: The methacrylic anhydride gelatin modified sulphoaluminate cement is prepared by the following method: S1. Using methacrylic anhydride and gelatin as raw materials to prepare methacrylic anhydride gelatin, adding the methacrylic anhydride gelatin into a phosphate buffer solution, stirring at 40° C. for 30-40 minutes, adding a silane coupling agent, and continuing to stir for 20-30 minutes to obtain a methacrylic anhydride gelatin solution; S2, grinding the sulphoaluminate cement clinker to obtain sulphoaluminate cement powder; S3. Place sulphoaluminate cement powder in a mixing tank, maintain the temperature in the mixing tank at 40-50°C under stirring at 150 rpm, use a spray gun to spray the methacrylic anhydride gelatin solution into the mixing tank at a spray pressure of 0.4 MPa, so that the methacrylic anhydride gelatin adheres to the surface of the sulphoaluminate cement particles, and dry at 55-60°C after spraying to obtain methacrylic anhydride gelatin-modified sulphoaluminate cement particles.
3. The high-performance dual-liquid slurry rapid-setting grouting material according to claim 1, characterized in that: The hydroxyethyl cellulose acrylamide modified bentonite is prepared by the following method: Preparation of hydroxyethyl cellulose-acrylamide graft polymer: hydroxyethyl cellulose and acrylamide are dispersed in deionized water and stirred on a magnetic stirrer, and then the pH is adjusted to 7 with a sodium hydroxide solution, and then the stirred solution is poured into a three-necked long-necked flask, and then an initiator is added, and the solution is placed in a MAS-Ⅱ microwave synthesis reaction station for synthesis reaction. The parameters of the synthesis reaction are preset to 40°C, 60 h, 200 W, and nitrogen is introduced. Under the action of magnetic stirring, a transparent colloidal liquid is obtained through synthesis reaction. After standing to room temperature, the reactant is precipitated with ethanol, and the precipitate is filtered after multiple washing to obtain a precipitate. The precipitate is dried to constant weight under a vacuum state at 70°C, and then purified with acetone in a Soxhlet extractor for 10 h. Finally, the precipitate is dried again to constant weight, and ground into powder in a YXQM planetary ball mill to obtain a hydroxyethyl cellulose-acrylamide graft polymer; Hydroxyethyl cellulose-acrylamide grafted polymer modified bentonite: Sodium bentonite was dispersed in deionized water, and 3 wt% of hydroxyethyl cellulose-acrylamide grafted polymer was added after the dispersion was fully stirred. The mixture was vigorously stirred for 2 h at a speed of 10×103 rpm using a GJD-B12K high-speed stirrer. Finally, the mixture was dried in a drying oven at 105°C±3°C to constant weight, and then ground to obtain hydroxyethyl cellulose acrylamide modified bentonite.
4. A high-performance dual-liquid slurry rapid-setting grouting material according to claim 3, characterized in that: The mass ratio of hydroxyethyl cellulose to acrylamide is 1:10, and ammonium persulfate and sodium bisulfite are used as initiators.
5. The high-performance dual-liquid slurry rapid-setting grouting material according to claim 1, characterized in that: The component A further comprises 0.06-0.08 parts of sodium citrate, 0.08-0.13 parts of sorbitol, and 1-2 parts of silica fume.
6. The high-performance dual-liquid slurry rapid-setting grouting material according to claim 1, characterized in that: The preparation method of the N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyltrimethylammonium chloride terpolymer is as follows: N-vinyl pyrrolidone is dissolved in water, methacrylic acid is added and stirred evenly, and then sodium hydroxide is used to adjust the pH to 7, and then 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride is added and stirred evenly to obtain a reaction solution; the reaction solution is added to a reaction container equipped with a stirrer, a thermometer and a nitrogen inlet, the temperature is increased and stirred, nitrogen is introduced, and the nitrogen introduction is stopped after the temperature is increased to 60° C., and potassium persulfate is added as an initiator, and the amount of potassium persulfate added is the total amount of N-vinyl pyrrolidone, methacrylic acid, and 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride. The reaction mixture was stirred for 2 hours at 60°C for 0.5% by weight, and then 6-tert-butyl-2,4-dimethylphenol was added as a polymerization inhibitor. The amount of 6-tert-butyl-2,4-dimethylphenol polymerization inhibitor added was 0.02% of the total mass of N-vinyl pyrrolidone, methacrylic acid, and 2-hydroxy-3-methacryloxypropyltrimethylammonium chloride. The reaction solution was then cooled to room temperature, precipitated, washed, dried, and crushed to obtain a terpolymer of N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyltrimethylammonium chloride.
7. The high-performance dual-liquid slurry rapid-setting grouting material according to claim 1, characterized in that: The amino acid type surfactant stimulant includes sodium lauroyl glutamate and sodium cocoyl alanine, and the mass ratio of sodium lauroyl glutamate to sodium cocoyl alanine is 3:
2.
8. The high-performance dual-liquid slurry rapid-setting grouting material according to claim 1, characterized in that: The redox initiator is an ammonium persulfate-sodium bisulfite redox agent; the photoinitiator includes 4,4'-dihydroxybenzophenone and nano-titanium dioxide, and the mass ratio of 4,4'-dihydroxybenzophenone to nano-titanium dioxide is 1:
1.
9. A method for preparing a high-performance dual-liquid slurry rapid-setting grouting material according to any one of claims 1 to 8, characterized in that: The following steps are involved: A. Preparing a first slurry: Component A is used as a raw material to prepare a first slurry. Sulphoaluminate cement modified with methacrylic anhydride gelatin and calcium powder are uniformly mixed to form a mixed powder. A corresponding amount of water is weighed according to the water-cement ratio. The water is first added to a mixing tank. Then, a stirrer matched with the mixing tank is turned on. The speed of the stirrer is 250 r / min. The internal temperature of the mixing tank is 35-40° C. The mixed powder is slowly added to the mixing tank at a speed of 250 r / min. After the mixed powder is added, the other components of component A are added to the mixing tank in sequence while the stirrer is continuously stirred. The stirring is continued for 10 minutes and then allowed to stand for 10 minutes to obtain a first slurry. B. Preparing a second slurry: dispersing the hydroxyethyl cellulose acrylamide modified bentonite in component B in water to obtain a bentonite dispersion; adding the N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride terpolymer in component B to water, heating to 50° C. under stirring, stirring at a constant temperature for 5-6 minutes, and then standing to cool to room temperature to obtain a N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride terpolymer solution; slowly pouring the N-vinyl pyrrolidone / methacrylic acid / 2-hydroxy-3-methacryloxypropyl trimethyl ammonium chloride terpolymer solution into the bentonite dispersion under stirring, stirring evenly to obtain a second slurry; C. At a rotation speed of 250 r / min, the first slurry and the second slurry are uniformly mixed, and then the dual initiator and the cross-linking agent in component B are added in sequence, and the target product is obtained after uniform stirring. The target product is a high-performance two-liquid slurry rapid-setting grouting material. The high-performance two-liquid slurry rapid-setting grouting material is used within 5 minutes after successful preparation. The high-performance two-liquid slurry rapid-setting grouting material is irradiated with ultraviolet light with a wavelength of 280-340 nm for 3-5 minutes in the initial stage of curing after the grouting is completed, so that the initial setting time of the high-performance two-liquid slurry rapid-setting grouting material is within 8 minutes, and the final setting time is 0.4-0.6h.
Citation Information
Patent Citations
Sulphoaluminate cement base synchronous slip casting material and preparation method
CN101693615A
Vinyl acetate-ethylene copolymer emulsion and polymer cement waterproof composition based on the same
CN104093679A
Method for synthesizing broad-spectrum amphoteric polyacrylamide emulsion
CN104387526A
Bone implant with both mechanical adaptability and osteogenic activity, and preparation method thereof
CN109106987A
Photosensitive controllable rapid-hardening concrete pouring material and construction method thereof
CN111499258A
Cited By
Grouting material, preparation method and application process
CN120841878A
Self-reinforced sound absorption cement-based material, preparation method and mix proportion design method
CN121005545A
Self-reinforced sound-absorbing cement-based material, preparation method and mix proportion design method
CN121005545B